TAMI-24. BEHAVIOR OF GLIOBLASTOMA STEM-LIKE CELLS WITH KNOWN IDH1 STATUS IN CEREBRAL ORGANOIDS. (9th November 2020) - Singh, Sanjay; Munyeshyaka, Maxime; Gumin, Joy; Yang, Jing; Ledbetter, Daniel; Hossain, Anwar; Kerrigan, Brittany Parker; Lang, Frederick
Abstract: Glioblastomas (GBM) exhibit high proliferative index, areas of necrosis, high vascularization, and are highly invasive to normal brain tissues. The most common and lethal form of GBMs are primary GBMs, with no prior clinical history. Whereas, secondary GBMs arise from low-grade gliomas and are associated with IDH1 mutation. Pre-clinical studies of GBM largely depend on patient-derived GBM stem-like cells (GSCs) in vitro and in vivo as orthotopic xenografts. Cerebral organoids (COs) derived from induced pluripotent stem cells can serve as allogenic in vitro model systems to study interactions between normal brain and GSCs. COs have been shown to harbor neural stem cells and their differentiated progenies as well as microglia within distinct niches. Here, we co-cultured 45 day-old COs and MDA-GSCs lines representing mesenchymal sub-group (M-MDA-GSC), classical sub-group (C-MDA-GSC), and IDH1 mutant ( IDH1 R132H -MDA-GSC). MDA-GSCs stably express fluorescent proteins and is used to track GSCs within COs. These GSC bearing COs were fixed, embedded, sectioned, immuno-stained, and imaged by confocal microscope. There was a positive correlation between GSC numbers in allografted niche and invasion into COs as measured from the edge of organoid, M-MDA-GSC (R 2 =0.99; 0.89μm/cell), C-MDA-GSC (R 2 =0.92; 0.66μm/cell), and IDH1 R132H -MDA-GSC (R 2 =0.89; 0.5μm/cell). Additionally, M-MDA-GSCs had significantly high percentage of Ki67 +ve invasive cells (24%) in comparison to C-MDA-GSCs (5.1%; p=0.0057). As a measure of interaction of MDA-GSC with normal cells, we assessed proximity of IBA1 +ve microglia in GSC niche within organoids and show that M-MDA-GSC and IDH1 R132H -MDA-GSC highly co-localized with IBA1 +ve microglia on day12 of co-culture. In conclusion, our cerebral organoid-based allograft study shows that mesenchymal GSCs (M-MDA-GSC) are most invasive whereas IDH1 mutant GSCs ( IDH1 R132H -MDA-GSC) are least invasive. C-MDA-GSCs are least proliferative while invading into normal COs. Uniqueness of CO based allograft system is highlighted by observed similarity between M-MDA-GSC and IDH1 R132H -MDA-GSC for their potential to attract IBA1 +ve microglia.